RELATIONSHIP OF WORKING SCHOOL ENVIRONMENT WITH JOB SATISFACTION OF TEACHERS IN GOVERNMENT SECONDARY SCHOOL IN LAHORE - Sonia; Ayesha Sagheer; Ayesha Anjum; Dr. Shamim Ullah (Policy Research Journal, 2025)
The study was conducted to investigate the relationship ofworking school environment with job satisfaction of teachers in government secondary schools of Lahore. The correlation research design was used for the study. The population of the study was 30 government secondary schools of Lahore. Convenient sampling technique was used to draw a sample of 500 (male=250, female=250) teachers. The instruments used in this studywere Teacher Job Satisfaction Questionnaire (TJSQ),School-Level Environment Questionnaire (SLEQ) and demographic Performa (age, gender and qualification).Descriptive (Mean, Standard Deviation and Frequency) and inferential statistics (Pearson-product moment correlation,Independent sample t-test and ANOVA) were used.The key conclusion based on descriptive and inferential statistics indicated that there was a significant relationship between working school environment and jobsatisfaction of teachers.It was identified that significant gender differences occur among teachers regarding their working school environment andjob satisfaction. The study indicates that there wasnon-significant relationship of age and qualification ofgovernment secondary schoolteachers with working school environment and job satisfaction.